Evaluasi Syzygium oleana Sebagai Tanaman Tepi Jalan (Studi Kasus Jalan Pulau Misol di Desa Dauh Puri Kauh) - Prastowo, Sunu Widhy; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2024)
Syzygium oleana is a decorative plant that used as potted roadside plants by the Government of Dauh Puri Kauh Village, Denpasar City. S. oleana that  were planted along Pulau Misol Street were severely damaged and lost their function as a decorative plant. To prevent further damage, it is necessary to evaluate the condition of the plants. The result of this evaluation will be used as references to make a planting and maintenancing plan so S. oleana plants can return to their functions as a decorative plants. This issn  observatory research, including inventory, analysis, synthesis and recommendations. The result is the recommendation of S. oleana planting plan and the maintenance schedule, including watering, fertilizing and pruning. S. oleana   were evaluated  based on it’s physical condition, function, spacing and it’s injuries.